A circus adventure - Bearn, Emily; Price, Nick (Egmont London, 2010)
General Marchmouse takes a toy bus for a joy ride and joins up with a mouse circus. But the travelling troupe is not what it appears to be, and he soon finds the village policemouse on his tail. Suggested level: primary